2011
DOI: 10.1590/s0365-05962011000600002
|View full text |Cite
|
Sign up to set email alerts
|

Dermatite seborreica

Abstract: Seborrheic dermatitis is a chronic relapsing erythematous scaly skin disease, the prevalence of which is around 1 to 3% of the general population in the United States. It has two incidence peaks, the first in the first three months of life and the second beginning at puberty and reaching its apex at 40 to 60 years of age. The prevalence of seborrheic dermatitis is higher in HIV-positive individuals and the condition tends to be more intense and refractory to treatment in these patients. Neurological disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 101 publications
0
64
1
13
Order By: Relevance
“…2 Our research revealed that 11.1% of seborrheic dermatitis patients had pityriasis amiantacea during follow-up. Unlike the 42% described in the literature, 5 all 63 patients presented with scalp involvement in our study. In relation to diagnostic investigation, a scalp biopsy was probably not performed because histopathology is not presented as a fundamental diagnostic criterion for the disease.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…2 Our research revealed that 11.1% of seborrheic dermatitis patients had pityriasis amiantacea during follow-up. Unlike the 42% described in the literature, 5 all 63 patients presented with scalp involvement in our study. In relation to diagnostic investigation, a scalp biopsy was probably not performed because histopathology is not presented as a fundamental diagnostic criterion for the disease.…”
contrasting
confidence: 71%
“…5 Others are emphatic in pointing out that the reaction is more common among children although it can occur at any age. 6 The prospective study of 85 PA cases revealed a mean age diagnosis of 23.8 years in the interval ranging from 5 to 63 – thus encompassing children and adolescents, with a female predominance.…”
mentioning
confidence: 99%
“…While SD affects all ages, it has a predominantly bimodal distribution, with a peak during infancy (2‐12 months of age) and another peak in early adulthood . Additionally, the incidence is higher among human immunodeficiency virus (HIV)‐infected and immunocompromised patients ranging from 30% to 83% .…”
Section: What Is Seborrheic Dermatitis?mentioning
confidence: 99%
“…The cause of SD is not completely understood, but it is often associated with Malassezia species (previously Pityrosporum), because this organism heavily colonizes sebum-rich skin [7]. For this reason, topical anti-yeast treatment is often effectively used for long-term control [8], while TCS and TCIs may be used to quickly minimize redness and scaling [9].…”
Section: Inflammatory Skin Conditionsmentioning
confidence: 99%